1986
DOI: 10.1007/bf00051506
|View full text |Cite
|
Sign up to set email alerts
|

Macrobenthic distribution and community structure in the upper navigation pools of the Upper Mississippi River

Abstract: The northern section of the Upper Mississippi River supports a diverse macrobenthic assemblage. Distribution of this benthic fauna, benthic community structure, and factors which influence both of these phenomena in these upper pools are reviewed. Dumping of heavy loads of municipal and industrial wastes from the Minneapolis-St. Paul metropolitan area has severely stressed the benthic community. Once abundant, pollution-sensitive mayflies, Hexagenia bilineata and H. limbata, are noticeably absent, replaced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Even though our study did not examine the difference in benthic communities between dike pools and other depositional areas (sand bars, silt bars, clay bank), previous large river studies have demonstrated that substrate composition is one of the factors directly influencing the diversity and abundance of benthic animals in these habitats (Anderson and Day, ; Beckett and Pennington, ). There is evidence that there may be an optimum distribution of particle sizes and quantity of organic matter for burrowing invertebrates such as midges (Chironomidae) and Hexagenia mayflies in depositional areas of large rivers (Eriksen, ; Wright and Mattice, ; Elstad, ). Sediments with more silt and clay retain higher amounts of organic matter (Culp et al , ; Hornbach et al , ) and are known to contain higher densities of macroinvertebrates (Carter et al , ; Anderson and Day, ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though our study did not examine the difference in benthic communities between dike pools and other depositional areas (sand bars, silt bars, clay bank), previous large river studies have demonstrated that substrate composition is one of the factors directly influencing the diversity and abundance of benthic animals in these habitats (Anderson and Day, ; Beckett and Pennington, ). There is evidence that there may be an optimum distribution of particle sizes and quantity of organic matter for burrowing invertebrates such as midges (Chironomidae) and Hexagenia mayflies in depositional areas of large rivers (Eriksen, ; Wright and Mattice, ; Elstad, ). Sediments with more silt and clay retain higher amounts of organic matter (Culp et al , ; Hornbach et al , ) and are known to contain higher densities of macroinvertebrates (Carter et al , ; Anderson and Day, ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by an important primary production (aquatic rooted macrophytes, perilithon and periphyton); the development of such vegetation resulting from the reduced current velocity and deposition of fine sediment (silt and clay), like in the deep and relatively quiet pools of the Missouri and the Mississippi rivers Elstad, 1986). All these environmental factors favour colonization of the dike field by specific lentic taxa (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Connections and submersions induce a high temporal variability of the habitat in the dike field and maintain a spatial diversity of the substrates (sand, in erosive zone and silty mud, in deposition areas). This double variability should act on the richness of the fauna (Elstad, 1986;Grzybkowska, 1989), but, without consideration of the Diptera Chironomidae, which contain a high number of species (Thieneman, 1954), no conclusion can be made on this point. On the second hand, connections and submersion induce an increase of the biological lateral exchanges (Amoros & Roux, 1988;Amoros, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Musculium transversum previously composed a substantial proportion of the density and biomass of the benthic fauna (Sparks, 1980;Elstad, 1986). In addition, fingernail clams had been important in the diets of certain waterfowl (particularly lesser scaup Aythya affinis; Gale, 1973;Thompson, 1973) and bottom-feeding fishes (Starrett, 1972;Jude, 1973).…”
Section: Discussionmentioning
confidence: 99%